Association between combination COVID-19-influenza vaccination and long COVID in middle-aged and older Europeans: A cross-sectional study - Wenyan Wu; Xiaowei Zheng; Huan Ding; Tongtong Miao; Yuhan Zang; Suwen Shen; Yumeng Gao (Human Vaccines & Immunotherapeutics)
The potential impact of combined COVID-19 and influenza vaccination on long COVID remains uncertain. In the present cross-sectional study, we aimed to investigate the plausible association between them in middle-aged and older Europeans based on the Survey of Health, Ageing, and Retirement in Europe (SHARE). A total of 1910 participants were recruited in the analyses. The study outcome was long COVID. Participants were divided into 4 groups through the self-reported status of COVID-19 and influenza vaccination. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated. 1397 participants experienced long COVID. After multivariable adjustment, those vaccinated with neither COVID-19 nor influenza vaccine had higher risk of long COVID (OR, 1.72; 95% CI, 1.26–2.35) compared to those vaccinated with both vaccines. Furthermore, adding the 4 statuses of COVID-19 vaccination/influenza vaccination to conventional risk model improved risk reclassification for long COVID (continuous net reclassification improvement was 16.26% [p = .003], and integrated discrimination improvement was 0.51% [p = .005]). No heterogeneity was found in the subgroup analyses (all p-interaction ≥0.05). Our study might provide a strategy for people aged 50 and over to reduce the occurrence of long COVID, that is, to combine the use of the COVID-19 vaccine and influenza vaccines.